Ultrasonic treatment of glassy carbon for nanoparticle preparation - Levêque, J.-M. (Elsevier B.V., 2017)
Glassy carbon particles (millimetric or micrometric sizes) dispersions in water were treated by ultrasound at 20 kHz, either in a cylindrical reactor, or in a “Rosette” type reactor, for various time lengths ranging from 3 h to 10 h. Further separations sedimentation allowed obtaining few nanoparticles of glassy carbon in the supernatant (diameter <200 nm). Thought the yield of nanoparticle increased together with the sonication time at high power, it tended to be nil after sonication in the cylindrical reactor. The sonication of glassy carbon micrometric particles in water using “Rosette” instead of cylindrical reactor, allowed preparing at highest yield (1–2 wt), stable suspensions of carbon nanoparticles, easily separated from the sedimented particles. Both sediment and supernatant separated by decantation of the sonicated dispersions were characterized by laser granulometry, scanning electron microscopy, X-ray microanalysis, and Raman and infrared spectroscopies. Their multiscale organization was investigated by transmission electron microscopy as a function of the sonication time. For sonication longer than 10 h, these nanoparticles from supernatant (diameter <50 nm) are aggregated. Their structures are more disordered than the sediment particles showing typical nanometer-sized aromatic layer arrangement of glassy carbon, with closed mesopores (diameter ∼3 nm). Sonication time longer than 5 h has induced not only a strong amorphization (subnanometric and disoriented aromatic layer) but also a loss of the mesoporous network nanostructure. These multi-scale organizational changes took place because of both cavitation and shocks between particles, mainly at the particle surface. The sonication in water has induced also chemical effects, leading to an increase in the oxygen content of the irradiated material together with the sonication time. © 2016 Elsevier B.V.